Emisariusze dziadowskiej tradycji – z problematyki lirniczej – przeszłość i teraźniejszość - Tomasz Rokosz (Edukacja Muzyczna, 2021)
The subject of the wandering beggars’songsand their functioning in culture hasbeen discussed many times in the Polish folklore studies and ethnomusicology. In the practical sense, it could seem that the beggars’song is a historical subject, closed a long time ago, similarly as hurdy-gurdy play-ing –one of its most interesting manifestations. Nevertheless, songs of hurdy-gurdy players have returned triumphantly these days, performed by amateur and professional musicians. Furthermore, we can observe the phenomenon of consolidation of musicians, not only into bands, but also in wider projects (festivals, academies, meetings of hurdy-gurdy players). The author presents a con-cise description of hurdy-gurdy playing traditions, the instrument itself, its song repertoire and the contemporary reconstruction of these traditions that is attempted by some environments.